A Guide to Scaling Resource Recovery & Reuse (RRR) Business Innovations in Africa and Asia - Danso, George K.; Drechsel, Pay; Cofie, Olufunke O. (CGIAR Research Program on Water, Land and Ecosystems, 2021)
Domestic waste is a continuously increasing urbanization challenge. Over the last decade, researchers with the International Water Management Institute (IWMI) have developed, tested and implemented (e.g. as PPP) a variety of RRR technologies and business models that simultaneously reduce the waste burden and support the return of resources like crop nutrients, biosolids and reclaimed water to agricultural production. The review compared over 20 scaling models and tools to identify those which best support the RRR innovations.